Assessment basics: How to implement an effective student learning assessment process - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2022)
Assessment Basics is a workshop focused on understanding the purpose behind student learning assessment, strategies to guide curricular integration, and techniques to use data for program improvement. Participants will be involved in leadership techniques to transfer into their own context. Experience with assessment processes will enable academic chairpersons with skills to guide faculty involvement and promote self-review of data that leads to continual program improvement.
Keywords: assessment; student learning; continual improvement; effectiveness; leadership skills